2020
DOI: 10.1186/s12959-020-00243-w
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum vertebral artery dissection: case report and review of the literature

Abstract: Background Hypertensive disorders of pregnancy are associated with vascular complications, including ischemic stroke and cervical artery dissection. Vertebral artery dissection (VAD), however, is rare. We describe a 31-year-old female who presented with vertigo, nausea, and vomiting and was found to have a VAD. In addition, we discuss the presentation, differential diagnosis, and pathogenesis of this uncommon but clinically significant vascular event and summarize other cases of vertebral artery dissection des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(22 reference statements)
0
10
1
Order By: Relevance
“…Women older than 35 years and those with a history of HDP or autoimmune disease (that is, systemic lupus erythematosus, anti-phospholipid syndrome) are particularly at high risk. Other predisposing factors of arterial dissection in the peripartum period include intimal injury related to Valsalva maneuvers during labor, alterations in arterial wall integrity due to pregnancy-related hormonal or vasoactive substances [ 9 ], and reactive thrombocytosis (subsequent to postpartum hemorrhage), which may all play potential roles in this process and require further investigation [ 16 ]. Moreover, prompt diagnosis and management of VAD are essential to ensure favorable patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Women older than 35 years and those with a history of HDP or autoimmune disease (that is, systemic lupus erythematosus, anti-phospholipid syndrome) are particularly at high risk. Other predisposing factors of arterial dissection in the peripartum period include intimal injury related to Valsalva maneuvers during labor, alterations in arterial wall integrity due to pregnancy-related hormonal or vasoactive substances [ 9 ], and reactive thrombocytosis (subsequent to postpartum hemorrhage), which may all play potential roles in this process and require further investigation [ 16 ]. Moreover, prompt diagnosis and management of VAD are essential to ensure favorable patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed hypothesis is dissection in the presence of an underlying structural defect of the arterial wall in the context of a connective tissue disorder, but most of the young women included in studies were not reported to present with such diseases. There is, however, evidence to support that the physiological changes that occur during pregnancy might contribute to artery dissection: that is, hemodynamic forces are intensified by increased blood volume and cardiac output, which can cause additional stress to the vessel walls, hormone-mediated changes concerning vasoactive substances, and collagen degradation [ 13 , 22 , 23 , 24 , 25 ]. A report by Salehi Omran et al (2020) offered results of an investigation into this area, which proved that pregnancy is an independent risk factor for CAD.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Prior literature on ppVADs has been limited by small sample sizes in case reports, making it difficult to compare ppVADs accurately with nonpostpartum VADs. 3,4,7,8,[11][12][13]16,17 We present the largest cohort of patients with postpartum VADs to date.…”
Section: Discussionmentioning
confidence: 99%
“…1 VADs occur in the postpartum period, but the majority of the literature on postpartum vertebral artery dissections (ppVADs) is in the form of case reports. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The largest cohort of VAD patients from a single institution consisted of 5 women with 6 VADs (1 being bilateral). 16 Despite accounting for only 2.4% of all spontaneous VADs, 4 ppVADs are devastating and have been documented to result in several deaths of otherwise healthy women.…”
mentioning
confidence: 99%